Opportunities and limitations in the counter-trafficking field: The experience of participating in Portuguese counter-trafficking networks - Clemente, M. (2022)
National and transnational collaborations and networks, within and across different sectors, are often described as critical elements of counter-trafficking efforts. This assumption has encouraged the proliferation in the Portuguese counter-trafficking field of national and local networks, bringing together governmental and non-governmental organizations to work on issues relating to “human trafficking”. Using autoethnography as a methodological and narrative tool, this article explores the type of collaboration and cooperation characterizing these cross-sectoral networks and the opportunities and limitations they bring, including the favouring of a substantial “victim-centered” approach to trafficking. The discussion argues that the differences in priorities, capital and power of network members help shape the opportunities and limitations of these networks, that are largely configured as an anti-politics instrument of the neoliberal counter-trafficking apparatus.